Penguatan Kapasitas Pelaku UMKM melalui Pembekalan Manajemen Usaha dan Strategi Pengembangan Bisnis di Kabupaten Samosir - Mislan Sihite; Ezekiel B. Sitorus; Siti Normi; Elperida J. Sinurat; Kristanty M. N. Nadapdap; Mangasa Panjaitan; Maludin Panjaitan; Jansen Hutabarat; Himpun Panggabean; Winarto; Henri Saragih (Jurnal Pengabdian Pada Masyarakat METHABDI, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a key pillar of the local economy in Samosir Regency, yet many business actors still face constraints such as limited capital, weak business management, restricted market access, and low utilization of technology. This community service activity aimed to provide MSME actors in Samosir Regency with knowledge and skills in business development strategy, covering product quality improvement, product innovation, marketing development, business management strengthening, and digital technology utilization. The activity was carried out through lecture, discussion, and mentoring methods involving MSME actors as partners. The results show that participants gained a better understanding of the factors influencing business development, the stages of business development from evaluation, planning, implementation, to monitoring and evaluation, as well as practical examples of business management such as the chicken egg business. This activity is expected to encourage MSME actors in Samosir Regency to manage their businesses more professionally and competitively.